2004
DOI: 10.1002/jmri.20217
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of diffusion tensor imaging to delineation of gliomas and glioblastomas

Abstract: Purpose: To determine if the diffusion tensor imaging (DTI) parameters fractional anisotropy (FA) and mean diffusivity (MD) can differentiate between accompanying edema and tumor cell infiltration of white matter (WM) beyond the tumor edge as defined from conventional MRI in low-and high-grade gliomas. Materials and Methods:We examined 12 patients with high-grade gliomas/glioblastomas and eight patients with low-grade gliomas and compared them to 10 patients with meningiomas, in which no tumor infiltration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
65
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 19 publications
11
65
3
5
Order By: Relevance
“…Fractional anisotropy values were significantly lower in all tumors than in adjacent and contralateral white matter. However, as others have also reported, 5,9,20,23,24 this index did not help in distinguishing between tumor grades. For example, Wieshmann et al 24 reported decreased FA values in pathological brain lesions that included low-and high-grade tumors, traumatic brain injury, perinatal infarcts and hypoxia, and cortical dysplasia.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Fractional anisotropy values were significantly lower in all tumors than in adjacent and contralateral white matter. However, as others have also reported, 5,9,20,23,24 this index did not help in distinguishing between tumor grades. For example, Wieshmann et al 24 reported decreased FA values in pathological brain lesions that included low-and high-grade tumors, traumatic brain injury, perinatal infarcts and hypoxia, and cortical dysplasia.…”
Section: Discussionmentioning
confidence: 59%
“…In a DT imaging study of peritumoral tissue in high-grade gliomas and metastatic lesions, Lu and coauthors 10 reported that the tumors can be distinguished based on mean diffusivity but not on FA values in the peritumoral tissue. Tropine et al 23 studied tumor tissue, white matter adjacent to the tumor, and white matter in the contralateral hemisphere in patients with tumors of different grades and types. These authors found that FA and mean diffusivity values are notably different between tumors in all tumor groups and contralateral white matter.…”
mentioning
confidence: 99%
“…Our results are consistent with Castillo (35), who found that the ADC values helped to distinguish high-grade glioma from normal tissue but could not be used to separate highgrade glioma from surrounding edema. Other studies (28,(34)(35)(36)(37)(38)(39)(40) have reported that high-grade tumors have significantly lower ADC values than low-grade and benign tumors and that peritumoral ADC is significantly higher in low-grade than in high-grade astrocytomas. In cases where the minimum ADC was considered, it was lower in high-grade gliomas than in the low-grade gliomas and appeared to be correlated well with tumor cellularity (26).…”
Section: Discussionmentioning
confidence: 98%
“…Also several studies have shown no significant difference for mean FA between low-and high-grade gliomas. [8][9][10] Secondary to these conflicting results, mean FA values may not be useful for the preoperative grading of cerebral gliomas.…”
mentioning
confidence: 99%